2004
DOI: 10.1016/j.jacc.2004.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in ventricular arrhythmia recurrence in patients with coronary artery disease and implantable cardioverter-defibrillators

Abstract: Women were less likely to experience VT/VF, and had fewer VT/VF episodes, than men. These findings were strongest in patients with evidence of a stable anatomic VT circuit: those with clinical or electrophysiologically induced VT. This study suggests that differing susceptibility to arrhythmia triggering may underlie the known differences in SCD rates between men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Recent analysis of the Multicenter Automatic Defibrillator Trial (MADIT) II population 1 has shown that while women in this trial had worse clinical status than males, they experienced fewer episodes of spontaneous ventricular tachycardia (VT) or ventricular fibrillation (VF). 2 This is consistent with data showing a decreased risk of VT/VF in females with coronary disease, 3 despite a greater predisposition among women to drug-induced proarrhythmia. 4 Previous work has suggested important gender differences in cardiac repolarization, with healthy women demonstrating significantly longer QT intervals.…”
Section: Introductionsupporting
confidence: 87%
“…Recent analysis of the Multicenter Automatic Defibrillator Trial (MADIT) II population 1 has shown that while women in this trial had worse clinical status than males, they experienced fewer episodes of spontaneous ventricular tachycardia (VT) or ventricular fibrillation (VF). 2 This is consistent with data showing a decreased risk of VT/VF in females with coronary disease, 3 despite a greater predisposition among women to drug-induced proarrhythmia. 4 Previous work has suggested important gender differences in cardiac repolarization, with healthy women demonstrating significantly longer QT intervals.…”
Section: Introductionsupporting
confidence: 87%
“…Although a reduced intensity of care may be, in part, related to a differential clinical history, symptom profile, and acuity of presentation, underrecognition of disease in women may also be contributory to worsening outcome, especially for women with an established diagnosis of IHD or acute MI (1,2,(23)(24)(25)(26). Of the 1.1 million hospitalizations for acute MI each year, more men are admitted through varying age groups (721,000 in men vs. 410,000 in women), with differences narrowing in elderly cohorts (2).…”
Section: Gender Differences In Ischemic Heart Disease (Ihd) Presentatmentioning
confidence: 99%
“…Of this symptomatic cohort, they more often have insignificant or non-obstructive coronary disease or less subclinical disease (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). As recently reported in the American College of Cardiology's National Cardiovascular Data registry in 375,886 patients referred for diagnostic left heart catheterization (45% women), the prevalence of obstructive coronary disease was less in women across all age (Ͻ50 to Ն80 years) groups (35).…”
Section: Gender Differences In Ischemic Heart Disease (Ihd) Presentatmentioning
confidence: 99%
“…This may result in a slightly lower use of defibrillators in women [25]. In addition, this may either reflect different psychological approaches to defibrillator therapy in women, or the "clinical experience" that women are less likely to suffer from sudden arrhythmic death or ventricular fibrillation, even when they already suffered from documented ventricular arrhythmias [39]. Results from the Multicenter UnSustained Tachycardia Trial (MUSTT) addressed the influence of gender on results of electrophysiological testing and outcome of patients [74].…”
Section: Prevention Of Sudden Death By Implantable Defibrillators In mentioning
confidence: 99%